Comparative Study of Autologous Stromal Vascular Fraction and Adipose-Derived Stem Cells for Erectile Function Recovery in a Rat Model of Cavernous Nerve Injury. (19th March 2015) - You, Dalsan; Jang, Myoung Jin; Kim, Bo Hyun; Song, Geehyun; Lee, Chunwoo; Suh, Nayoung; Jeong, In Gab; Ahn, Tai Young; Kim, Choung-Soo
Abstract : The abilities of intracavernous injection of autologous stromal vascular fraction (SVF) and adipose-derived stem cells (ADSCs) to facilitate recovery of erectile function in a rat model of cavernous nerve injury were compared. Intracavernous injection of SVF significantly improved erectile function compared with that in the control group, whereas the ADSC group showed marginally significant improvement. The increases in the smooth muscle/collagen ratio and von Willebrand factor expression were larger in the SVF group than in the ADSC group. Both cell types are equally effective in recovering penile erection, but SVF may be superior to ADSCs in terms of histomorphometric changes. Abstract: The abilities of intracavernous injection of autologous stromal vascular fraction (SVF) and adipose-derived stem cells (ADSCs) to facilitate recovery of erectile function in a rat model of cavernous nerve (CN) injury were compared. Forty male Sprague-Dawley rats were randomly divided into four groups: sham and control groups (intracavernous injection of phosphate-buffered saline), SVF group (intracavernous injection of SVF), and ADSC group (intracavernous injection of ADSCs). Rats in the latter three groups underwent bilateral CN injury prior to injection. The evaluation of erectile function and histomorphometric studies were performed 4 weeks after injection. The ratio of maximal intracavernous pressure to mean arterial pressure was significantly lower in the control group than in the sham group (0.18 vs. 0.56, p < .001). Intracavernous injection of SVF (0.36, p = .035) significantly improved erectile function compared with that in the control group, whereas the ADSC group (0.35, p = .052) showed marginally significant improvement. The smooth muscle/collagen ratio, smooth muscle content, number of neuronal nitric-oxide synthase-positive nerve fibers, and expression of von Willebrand factor were significantly higher in the SVF and ADSC groups than in the control group. Expression of endothelial nitric-oxide synthase was significantly increased in the SVF group. The increases in the smooth muscle/collagen ratio and von Willebrand factor expression were larger in the SVF group than in the ADSC group. Intracavernous injection of SVF or ADSCs was equally effective in recovering penile erection in a rat model of CN injury.